ABCG2: the lateral slice hypothesis as a model for multidrug transport - Cox, Megan H. (2019)
ABCG2 (also known as BCRP) is an efflux ABC transporter recognised to export a wide range of substances. ABCG2 is widely distributed in humans, predominantly residing within tissues which have protective roles, such as the intestine and blood brain barrier. ABCG2 is known for its role in the clinical phenomenon of multidrug resistance, particularly in limiting the exposure to chemotherapeutic agents. Despite this significant role in tissue exposure to xenobiotics, exactly how ABCG2 binds and transports a wide range of structurally unrelated drug substrates remains unknown.